2014
DOI: 10.1016/j.injury.2013.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in severely injured patients depends on psychosocial factors rather than on severity or type of injury

Abstract: The experience of impaired QOL appears to depend on living alone, inability to return to work and pre-accidental comorbidity rather than on the injured body area or the severity of the injury. Duration of hospital or ICU stay is important to subsequent QOL, even if ISS or body region is not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
41
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 36 publications
9
41
2
2
Order By: Relevance
“…Patients who cannot regain their previous job or become unemployed may experience lower QOL, but it is also possible that patients with decreased QOL need more time to return to work. Age and ISS were not related to QOL in our study population, 24 although older patients and more severely injured patients reported more physical limitations. Older patients may have accepted their physical limitations easier because they might be used to the expectation of physical limitations due to ageing.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Patients who cannot regain their previous job or become unemployed may experience lower QOL, but it is also possible that patients with decreased QOL need more time to return to work. Age and ISS were not related to QOL in our study population, 24 although older patients and more severely injured patients reported more physical limitations. Older patients may have accepted their physical limitations easier because they might be used to the expectation of physical limitations due to ageing.…”
Section: Discussioncontrasting
confidence: 50%
“…The mean time since the injury was 2.8 (SD 0.9) years. Most patients were males (69%), with a mean age of 46 (SD 19) years and a median ISS of 21 (interquartile range [17][18][19][20][21][22][23][24][25][26][27]. The most common injury was intracranial injury (61%), and 86% of the patients had received ICU treatment (table 1).…”
Section: Patientsmentioning
confidence: 99%
“…In a former study, injury type, age, gender, length of hospital stay, intensive care unit (ICU) days, injury severity, post-traumatic stress symptoms and return to work were found to be associated with functional outcome and recovery 25 26. Furthermore, important determinants of long-term disability after trauma are patients with one or more comorbidities,29 patients with multiple injuries30 and frailty in elderly patients 31 32…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pain was found to be a major predictor for psychological adjustment problems two years after injury 16 . ASD, PTSD, and psychological distress are positively associated with wound healing and fatigue 13,[20][21][22][23][24][25] and negatively with quality of life (QOL) compared to the general population 18,[26][27][28][29][30][31] . Also, patients' satisfaction with work status, general health, and recovery from injury are related with impaired mental health, depressive symptoms, and increased risk of substance abuse 30,32 .…”
mentioning
confidence: 99%
“…Psychosocial problems and disorders can have a negative impact on patients' lives up to years later 13,[16][17][18] . For instance, 45% of the patients could not pursue with leisure activities and 27% reported a broken marriage six years after trauma 19 .…”
mentioning
confidence: 99%